Evolución de los estilos de liderazgo y su impacto en la gestión de la organización Prodepol (2021)
This text addresses the importance of leadership as a competence in organizations and, in the same way, the importance of having a training plan for this competence for workers who are in positions that handle personnel. The different theories that have been developed in history about leadership are addressed, as well as their study approaches and the different styles that have been generated throughout history, highlighting this competence in the human talent management process and as an aid. to him good development of activities. This was carried out by the compilation of the writings produced in the formal education environment and the books found in the search engines and databases that the Universidad América provides to its students.